NILA : A NATIONAL INFORMATION LITERACY AGENDA FOR MALAYSIA - Edzan, N.N.; Mohd Saad, Mohd Sharif (Malaysian Journal of Library and Information Science, 2005)
Information literacy is defined as the ability to recognize when information is needed and the ability to locate, evaluate, and use effectively the needed information. It has been a subject for discussion amongst librarians and information professionals since the 1970’s and there are numerous information literacy initiatives that are in place in educational institutions worldwide. This paper attempts to look at the information literacy initiatives in Malaysia and proposes a framework for the implementation of a National Information Literacy Agenda (NILA).